STRUKTUR TEKS MIKTO PADA CHANNEL YOUTUBE NAJWA SHIHAB KAJIAN WACANA KRITIS TEUN A. VAN DIJK - Widya Widya; Mahmudah Mahmudah; Muhammad Rapi (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
In language studies there are studies that function to understand language in its use. This intends to help listeners and readers to understand the implied meaning in a text, especially in critical discourse studies. Teum A. Van Dijk divides the function of language into four namely ideology, domination, power, influence. The object of study in this analysis is a video entitled "Najwa's notes with Maudy Ayunda" on the Najwa Shihab Youtube Channel. From the results of the macro structure analysis on the use of the word modality, the data for the word modality wants is 1, the word modality wants is 1, the word modality must be 1, the word modality will be 1, the word modality can be 3.